Grey Evaluation Method of DC Current Transformer Transient Characteristics in High-Voltage Transmission System. Issue 3 (July 2021) - Ji, Feng; Lu, Shufeng; Xu, Minrui; Chen, Gang; Lu, Zigang; Guo, Jiahao
Abstract: The transient characteristics of the current transformer and its evaluation method are the key factors affecting the protection device, system security, and stability. Therefore, to verify and evaluate the rise time, maximum overshoot, transient delay, and periodic stability of the DC transformer, a DC transformer calibration system is proposed. Based on the calibration system, the index basis of transformer evaluation is obtained, and the evaluation method of DC transformer characteristics based on grey theory is proposed. Finally, through the transient performance test, the transient characteristic parameters of the tested DC transformer are obtained, and its evaluation model is established. Through case analysis, the quantitative evaluation scores of different transformers are given. The method proposed in this paper has an important reference value in the field calibration of the DC transformer.